Nandrolone (17-Nortestosterone) And Glucose Metabolism: From Ugly Duckling To Handsome Swan - Sanjay Kalra; Atul Dhingra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Glucosarcopenia, or sarcopenia coexisting with diabetes,is a common condition. Caused by various factors,including poor glucose control, as well as some glucoseloweringtherapies, sarcopenia negatively impacts qualityof life and long-term health. Nandrolone, or 19-nortestosterone, is a selective anabolic receptormodulator (SARM), classified as an anabolic-androgenicsteroid (AAS). A review of its pharmacological propertiessuggests that it may be used as therapy for sarcopenia,along with medical nutrition therapy and resistanceexercise training. This review suggests a practical andpragmatic approach towards ensuring safe and smartusage of nandrolone in glucosarcopenia management. Keywords: Anabolic steroid, androgenic steroid,diabetes, glucosarcopenia, muscle health,musculoskeletal health, sarcopenia